Upaya Pengembangan Budaya Literasi oleh Mahasiswa KKN melalui Kegiatan Membuat Proyek Berbasis Isi Buku Bacaan : Studi Kasus SDN 3 Krisak - Huda Karunia Al Rasyid; Ichsan Abror; Bardhian Cahyo Aji Gumilang; Amalia Rosyida; Laila Nur Hasanah; Farah Nur Azizah; Raudatul Intan Elok Mutiyara; Gea Nada Aderangga; Restan Oskarina; Leny Nuraini; Arinda Safira (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The low reading interest and literacy skills of elementary school children in Indonesia remain a problem that requires creative and sustainable solutions. Factors such as limited access to quality books, a lack of reading habits at home, and uninteresting learning approaches are often the causes of a weak literacy culture among students. To address this problem, the Student Community Service Program (KKN) of Sebelas Maret University students in Singodutan Village implemented an activity aimed at fostering a culture of literacy in children through a Reading Book Content-Based Project at SDN 3 Krisak. The concept of this activity integrates reading activities with the creation of creative projects that are appropriate to the content of the reading, so that students not only understand the text but are also able to process the information into real products. This study used a qualitative approach with a phenomenological research type to understand students' experiences during the activity. Data were collected through observation, documentation, and literature review, which were then analyzed descriptively. Activities included selecting reading books appropriate to students' ability levels, shared reading, discussions about the reading content, and the creation of creative projects such as posters, picture stories, or artwork inspired by the reading material. The results of the activity showed an increase in student participation in reading activities, an increase in interest in books, and an improvement in their ability to process information into creative works. Furthermore, students demonstrated greater self-confidence when presenting their work to their classmates.